Determination of Patulin Using Amperometric Tyrosinase Biosensors Based on Electrodes Modified with Carbon Nanotubes and Gold Nanoparticles - R.M. Varlamova; E.P. Medyantseva; R.R. Hamidullina; H.C. Budnikov (Учёные записки Казанского университета: Серия Естественные науки)
New amperometric biosensors based on platinum screen printed electrodes modified with multiwalled carbon nanotubes, gold nanoparticles, and immobilized enzyme – tyrosinase have been developed for determination of patulin in the concentrations of 110–6 – 810–12 mol/L with an error of no more than 0.063. The best conditions for obtaining gold nanoparticles have been chosen. The conditions for immobilization of multi-walled carbon nanotubes and gold nanoparticles on the surface of the planar electrode have been revealed. The conditions for functioning of the proposed biosensors have been identified. The results have been used to control the content of patulin in food products within and lower than the maximum allowable levels.